Effect of smear layer removal agents on the microhardness and roughness of radicular dentin - Hosea Lalrin Muana (Elsevier, 2021)
Purpose: To evaluate the effect of phytic acid (IP6) on the surface roughness and microhardness of human root canal dentin and compare it to other smear layer removal agents. Materials and methods: Fifty extracted human maxillary incisors were sectioned longitudinally into a total of 100 specimens followed by embedding in auto-polymerizing acrylic resin. The specimens were polished and then randomly divided into five groups (n = 20) according to the test solution used to condition root canal dentin: 17% ethylenediaminetetraacetic acid (EDTA); 10% citric acid (CA); 1% IP6; 37% phosphoric acid (PA); or distilled water (control group). Each specimen was treated with a total volume of 1 ml of each solution for 1 min with agitation. Each group was then divided into two subgroups of 10 specimens each. The specimens of the first subgroup were used to determine microhardness, using Vickers hardness tester, and the specimens of the second subgroup were used to measure surface roughness, using a confocal laser scanning microscope. The results were analyzed statistically using one-way ANOVA and Tukey tests, α = 0.05. Results: All the tested groups exhibited microhardness and surface roughness values that were statistically significantly different when compared with the control group (P < 0.05). The microhardness value obtained with IP6 was significantly lower when compared to EDTA, CA, and the control group, whereas its roughness value was significantly higher compared to the aforementioned groups. However, there was no significant difference between IP6 and PA (P > 0.05). Conclusions: IP6 and PA showed the lowest microhardness and the highest surface roughness values.